Influence of artificial drainage system design on the nitrogen attenuation potential of gley soils: Evidence from hydrochemical and isotope studies under field-scale conditions. (15th January 2018) - Clagnan, E.; Thornton, S.F.; Rolfe, S.A.; Tuohy, P.; Peyton, D.; Wells, N.S.; Fenton, O.
Abstract: In North Atlantic Europe intensive dairy farms have a low nitrogen (N) use efficiency, with high N surpluses often negatively affecting water quality. Low feed input systems on heavy textured soils often need artificial drainage to utilise low cost grassland and remain profitable. Heavy textured soils have high but variable N attenuation potential, due to soil heterogeneity. Furthermore, drainage system design can influence the potential for N attenuation and subsequent N loadings in waters receiving drainage from such soils. The present study utilises end of pipe, open ditch and shallow groundwater sampling points across five sites in SW Ireland to compare and rank sites based on N surplus, water quality and "net denitrification", and to develop a conceptual framework for the improved management of heavy textured dairy sites to inform water quality N sustainability. This includes both drainage design and "net denitrification" criterion, as developed within this study.N surplus ranged from 211 to 292 kg N/ha (mean of 252 kg N/sourha) with a common source of organic N across all locations. The predicted soil organic matter (SOM) N release potential from top-subsoil layers was high, ranging from 115 to >146 kg N/ha. Stable isotopes analyses showed spatial variation in the extent of specific N-biotransformation processes, according to drainage location and design. Across all sites, nitrate (NO3 -N) was converted to ammonium (NH4 + -N), which migrated offsite through open ditch and shallow groundwater pathways. Using the ensemble data the potential for soil N attenuation could be discriminated by 3 distinct groups reflecting the relative dominance of in situ N-biotransformation processes deduced from water composition: Group 1 (2 farms, ranked with high sustainability, NH4 + < 0.23 mg N/l, δ 15 N-NO3 − > 5‰ and δ 18 O-NO3 − > 10‰), low NH4 + -N concentration coupled with a high denitrification potential; Group 2 (1 farm with moderate sustainability, NH4 + < 0.23 mg N/l, δ 15 N-NO3 − < 8‰ and δ 18 O-NO3 − < 8‰), low NH4 + -N concentration with a high nitrification potential and a small component of complete denitrification; Group 3 (2 farms, ranked with low sustainability, NH4 + > 0.23 mg N/l, 14‰ > δ 15 N-NO3 − > 5‰ and 25‰ > δ 18 O-NO3 − > −2‰), high NH4 + -N concentration due to low denitrification. The installation of a shallow drainage system (e.g. mole or gravel moles at 0.4 m depth) reduced the "net denitrification" ranking of a site, leading to water quality issues. From this detailed work an N sustainability tool for any site, which presents the relationship between drainage class, drainage design (if present), completeness of denitrification, rate of denitrification and NH4 -N attenuation was developed. This tool allows a comparison or ranking of sites in terms of their N sustainability. The tool can also be used pre-land drainage and presents the consequences of future artificial land drainage on water quality and gaseous emissions at a given site. Highlights: N attenuation capacity is altered by drainage installation and design. Groundwater drainage systems maintain higher attenuation than shallow systems. Isotopic measurements provide quantified data for net denitrification. Net denitrification is an efficient monitoring tool to rank farm sustainability.